KECEMASAN MAHASISWA PERAWAT UNIVERSITAS NUSANTARA PGRI KEDIRI SELAMA PEMBELAJARAN JARAK JAUH - Tri Wijayanti, Endah; Risnasari, Norma; Dewi Aisyah, Septi (Universitas Nusantara PGRI Kediri, 2021)
The Covid-19 pandemic has had the impact of changing new learning methods for students. The change in providing distance lectures during the pandemic has created new habits in the learning process. These changes have a psychological impact on students. This study aims to determine how the level of student anxiety in dealing with online learning. This study used a descriptive design with a sample of all students who studied nursing at the Nusantara University PGRI Kediri. The results of this study are that the level of mild anxiety is 4%, moderate is 81%, and severe is 15%. The conclusion in this study is that students feel anxiety at a moderate level in dealing with distance learning. Therefore, by conducting online psychoeducation to students about anxiety and how to manage anxiety during distance learning, it is hoped that it will increase student awareness so that the learning process runs effectively and efficiently.